2020
DOI: 10.25135/rnp.159.19.08.1384
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR-Based Metabolomics of Clinacanthus nutans Leaves Extracts in Correlation with Their Anti-neuroinflammation Towards LPS-Induced BV2 Cells

Abstract: The metabolomics approach successfully explained the possible neuroprotective effect of Clinacanthus nutans (Burm. f.) Lindau (CN) leaf extracts. Forty-four metabolites were putatively identified via proton Nuclear Magnetic Resonance ( 1 H NMR and J-resolved NMR) metabolic profiling of CN leaf extracts in three types of solvents, namely water, 50% ethanol, and ethanol. Metabolite fingerprinting has efficaciously differentiated aqueous between the other two extracts. The variable importance of projection (VIP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…Putative identification revealed forty-four metabolites including triterpenes, sulfur-containing glycosides, C -glycosyl flavones, and a variety of other compounds including sugars, amino acids, and phenolics [ 15 – 17 , 21 ]. The present study of CNE showed a similar 1 H NMR spectroscopic pattern [ 15 ], with a high intensity of the shaftoside resonance [ 16 , 17 ]. In our recent report on CNE phytoconstituents with NO inhibitory activities in the BV2 cell assay revealed 30 key chemical markers, namely schaftoside, acetate, propionate, alanine, clinacoside C, monoacyl-monogalactosylglycerol, fructose, clinacoslides A and B, ascorbic acid, a mixture of cerebrosides, choline, stigmasterol- β -glucoside, citric acid, valine, catechin, orientin, chlorogenic acid, leucine, butyrate, cycloclinacosides A1 and A2, sucrose, vitexin, β -sitosterol, β -glucose, vanillic acid, gendarucin A, betulin, and isoleucine [ 16 ].…”
Section: Resultssupporting
confidence: 56%
See 4 more Smart Citations
“…Putative identification revealed forty-four metabolites including triterpenes, sulfur-containing glycosides, C -glycosyl flavones, and a variety of other compounds including sugars, amino acids, and phenolics [ 15 – 17 , 21 ]. The present study of CNE showed a similar 1 H NMR spectroscopic pattern [ 15 ], with a high intensity of the shaftoside resonance [ 16 , 17 ]. In our recent report on CNE phytoconstituents with NO inhibitory activities in the BV2 cell assay revealed 30 key chemical markers, namely schaftoside, acetate, propionate, alanine, clinacoside C, monoacyl-monogalactosylglycerol, fructose, clinacoslides A and B, ascorbic acid, a mixture of cerebrosides, choline, stigmasterol- β -glucoside, citric acid, valine, catechin, orientin, chlorogenic acid, leucine, butyrate, cycloclinacosides A1 and A2, sucrose, vitexin, β -sitosterol, β -glucose, vanillic acid, gendarucin A, betulin, and isoleucine [ 16 ].…”
Section: Resultssupporting
confidence: 56%
“…Khoo et al . also successfully demonstrated through HPLC-DAD-ESI-MS/MS quantification that four metabolites, namely shaftoside (0.65±0.03 mg/g), isovitexin (0.128±0.007 mg/g), orientin (0.005±0.00 mg/g), and isoorientin (0.004±0.000 mg/g), were present in the CNE, wherein all these four constituents were also identified in the current study [ 15 , 16 ].…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations